ICT-Based Learning Media Implementation Training to Improve Digital Literacy of SMA Negeri 1 Tanjung Raja Teachers - Camellia; Chotimah, Umi; Yadi, Farhan; Yulianda, Klarissa; Novriantara, Tri Satya (Pascasarjana Universitas Mataram, 2025)
Training on the use of ICT-based learning media was held to improve teachers' digital literacy at SMA Negeri 1 Tanjung Raja. This program is divided into two stages to strengthen teachers' ability to create and apply digital learning media that is interesting, interactive, and relevant to their needs. The goal is to give teachers practical skills in using digital platforms such as Canva, Wordwall, Wayground (Quizizz), and CapCut when teaching. The method of implementation includes opening, explanation of the material, direct practice, and assessment through pretest and posttest to measure the improvement of participants' understanding. The results of the assessment showed an increase in the average score of participants from 50.52 to 55.05 from a total of 57 people, indicating a significant increase in mastery of ICT-based learning media. The response of the participants was very good, as evidenced by the activeness in the discussion, the willingness to try the media, and the seriousness in making learning products. The program is planned to be continuous with the product presentation stage, the application of media in the classroom, and practical guidance and assessment. It is hoped that this activity can be an important step in supporting digital learning changes at the high school level.